Le discours direct dans la presse : une approche didactique - Grégoire LACAZE (E-REA, 2019)
This paper offers a synthesis of recent research works focusing on direct reported speech used in the British press. Thanks to a didactic approach, it aims to analyse the way reported words are inserted into newspaper articles. It emphasizes some specificities of utterances of direct speech that are linked to the stylistic norms of journalistic discourse. Various strategies of anonymizing reported sources are also investigated.